Penerapan Sistem Pemerintahan Masyarakat Adat Nagari di Kecamatan Pauh Kota Padang - Rahayu, Putri Indah; Mubarak, Adil (Lembaga Yasin AlSys, 2025)
The nagari government, a local governance system rooted in customary law in West Sumatra, faces significant challenges in integrating with the formal governmental system. This study aims to provide an in-depth understanding of the implementation of the customary governance system in the nagari communities of Pauh District, Padang City, using a qualitative case study approach grounded in Van Metter and Van Horn’s policy implementation theory. Data were collected through observation, in-depth interviews, and documentation in two nagari, Nagari Pauh V and Nagari Limau Manis. Informants were purposively selected and included ninik mamak (traditional leaders), customary figures, village officials, and members of the customary community. Data analysis followed the Miles and Huberman model, involving data reduction, data presentation, and conclusion drawing, with validation through source and technique triangulation. The findings reveal that the implementation of the customary governance system has not been optimal due to a lack of harmonized understanding between traditional and formal actors, limited human and financial resources, weak inter-institutional coordination, and insufficient structural support from local government. Furthermore, the commitment of traditional actors has not been fully aligned with the support of formal institutions. These findings suggest the need for more adaptive and integrative policies to ensure that customary institutions have a substantive rather than symbolic role in local governance.